The effect of nematodes on larvae of Phyllophaga menetriesi and Anomala inconstans (Coleoptera: Melolonthidae) - MELO-MOLINA, ELSA LILIANA; ORTEGA-OJEDA, CARLOS ALBERTO; GAIGL, ANDREAS (Revista Colombiana de Entomología, 2007)
The complex of rhizophagous white grubs that includes Phyllophaga menetriesi and Anomala inconstans affects a wide range of commercial crops, generating severe yield losses in Colombia. one environmentally sustainable alternative for their control is the use of entomopathogenic nematodes (EPN’s). Understanding that certain developmental stages of pests are more susceptible to these microorganisms, we studied the effects of the entomonematodes Heterorhabditis sp. (HNI-Cenicafé) and Steinernema feltiae (Sf-Villapinzón) on the mortality of different stages of these two white grubs species [L1, L2, L3 young, L3 mature (L3m) and Prepupae (Pp)]. Under controlled laboratory conditions (24.5ºC and 70 ± 5% R. H.), we applied a concentration of 10,000 Ijs/ml to larvae maintained in organic soil, evaluating their effect 10 and 20 days after inoculation (dAI). The EPN strains caused different mortality rates on A. inconstans (P ≤ 0.05), with higher mortality for HNI (84.7%) than Sf (76.7%) for the different instars, although L2 was more susceptible to the first strain (98.3%). No differences were observed between evaluation times for these species. The greatest mortality in P. menetriesi occurred at 20 dAI with HNI, where L2 was also the most susceptible stage (81.1%). It was determined that the susceptibility of white grubs to EPN’s depends on the host species as well as the EPN strain used.  These findings are as important as knowledge of pest dynamics in order to be able to develop strategies for the biological control of white grubs.